Implementasi Pemberian Remisi Narapidana Narkotika Dan Mekanisme Pelaksanaanya Menurut Perarturan Pemerintah No 99 / 2012 - risyal hardiyanto hidayat (Universitas Widya Gama Malang, 2020)
Narcotics crime in Indonesian is very often discussed because the impact can be physical, mental health, emotional, attitude in society and can damage the younger generation, besides that the type of narcotics crime is a problem that continues to spread in various countries. Republic of Indonesia as a country based on the law of existence to achieve a better life in society. If someone does something which is a crime, then someone will be punished. However, during the sentence there was a reduction in the sentence or remission. In correctional institutions, remission is regulated in the Correctional Law of 1995 Article 14 Paragraph 1 regarding the rights of prisoners in item (i). The purpose of this study was to determine how the implementation of the mechanism for granting remission rights to narcotics prisoners. The method used is descriptive qualitative research method with normative legal research. Data collection techniques with literature study. The results showed that the implementation of the provision of remission rights still has problems, namely regarding the provision of Justice Collaborator as a term and condition of Law No. 99/2012.